Bahasa Minoritas Enggano di Beranda Depan NKRI: Kontak dan Gejala Kepunahan Bahasa di Pulau Enggano, Bengkulu - Indonesia: CONTACTS AND SYMPTOMS OF LANGUAGE EXTINCTION ON ENGGANO ISLAND, BENGKULU INDONESIA - Fanny Henry Tondo (Jurnal Masyarakat dan Budaya, 2023)
Enggano is an outermost island facing the west coast of Sumatra Island, precisely located in BengkuluProvince. On this island, you can find the Enggano language and other languages spoken by various ethnicimmigrants such as Javanese, Malay, Padang, Batak, and Bugis. The Enggano language itself is spoken in severalvillages such as Meok, Apoho, Malakoni, Kaana, Khayapu, and Banjarsari villages. The strong use of the languagecan be observed in the villages of Meok, Apoho, and Malakoni, while in the last three villages it has begun toerode due to interaction with ethnic immigrants. This qualitative research was conducted on Enggano Island,Bengkulu, as part of the 2015 LIPI expedition called the Widya Nusantara Expedition (EWIN) which involvedvarious disciplines, both natural and social sciences. In collecting data, observation and in-depth interviews wereused to determine the linguistic situation, especially language contact and the symptoms of language extinction.This study shows that language contact between the Enggano people who speak Enggano and the immigrants withtheir respective languages is very strong in the villages of Banjarsari, Kaana, and Khayapu, causing symptomsof language extinction. Meanwhile, the Enggano language in the villages of Meok, Apoho, and Malakoni is stillquite able to survive because the population is homogeneous with Enggano people and has not been mixed withimmigrants much.